An Eco-Friendly Method of BaTiO3 Nanoparticle Synthesis Using Coconut Water. (17th July 2018) - Gomes, Maria de Andrade; Magalhães, Lucas Gonçalves; Paschoal, Alexandre Rocha; Macedo, Zélia Soares; Lima, Álvaro Silva; Eguiluz, Katlin Ivon Barrios; Salazar-Banda, Giancarlo Richard
Abstract : BaTiO3 nanoparticles were successfully synthesized by a new coconut water-based sol–gel method using Ba(CH3 COO)2 and TiCl3 as the starting salts. The influence of the amount of coconut water and calcination conditions on the barium titanate crystallization was investigated. The resulting nanoparticles were characterized by thermogravimetric and differential thermal analysis, X-ray diffraction, scanning electron microscopy, and Raman and Fourier transform infrared (FTIR) spectroscopies. The ferroelectric tetragonal single phase of BaTiO3 was obtained in samples prepared with a ratio of coconut water volume (mL)/BaTiO3 mass (g) of 25 : 2 and 30 : 2, calcined at 1100°C, which was confirmed by XRD measurements. Crystallites with an average size of about 31 nm for both samples were obtained, and microscopy images revealed the presence of particles in the range of 40 to 60 nm. Raman and FTIR spectra confirmed the dominant tetragonal phase of BaTiO3, meanwhile traces of BaCO3 were identified in FTIR spectra.